2023
DOI: 10.1186/s12967-023-04153-z
|View full text |Cite
|
Sign up to set email alerts
|

LINC00963-FOSB-mediated transcription activation of UBE3C enhances radioresistance of breast cancer cells by inducing ubiquitination-dependent protein degradation of TP73

Yansu Wang,
Ming Liu,
Xiaoqian Liu
et al.

Abstract: Background The ubiquitin protein ligase E3C (UBE3C) has been reported to play an oncogenic role in breast cancer (BRCA). This work further investigates the effect of UBE3C on the radioresistance of BRCA cells. Methods Molecules linking to radioresistance in BRCA were identified by analyzing two GEO datasets, GSE31863 and GSE101920. UBE3C overexpression or knockdown was induced in parental or radioresistant BRCA cells, followed by irradiation treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…An examination into the mechanism of action found that LINC00963 can interact with microRNA-625 (miR-625). LINC00963 inhibited the inhibitory impact of miR-625 on high mobility group AT-hook 1 (HMGA1) in breast cancer cells by acting as a ceRNA for miR-625 (Wu et al, 2020) (Wang et al, 2023). Our results about the gene expression pattern of LINC00963 validated our bioinformatics analyses, but it was different from previous investigations.…”
Section: Discussionsupporting
confidence: 64%
“…An examination into the mechanism of action found that LINC00963 can interact with microRNA-625 (miR-625). LINC00963 inhibited the inhibitory impact of miR-625 on high mobility group AT-hook 1 (HMGA1) in breast cancer cells by acting as a ceRNA for miR-625 (Wu et al, 2020) (Wang et al, 2023). Our results about the gene expression pattern of LINC00963 validated our bioinformatics analyses, but it was different from previous investigations.…”
Section: Discussionsupporting
confidence: 64%
“…An analysis of the Gene Expression Omnibus (GEO) databases GSE31863 and GSE101920 revealed the upregulation of the E3 ligase UBE3C in breast cancer tissue samples, and its elevation correlated with adverse radiological responses. Correlation experiments were conducted on molecules upstream and downstream of UBE3C; LINC00963 activates UBE3C transcription by facilitating the nuclear translocation of FOSB, and UBE3C catalyzes the ubiquitination degradation of the tumor suppressor TP73, thus enhancing the radioresistance of tumor cells [62]. Similarly, ubiquitinconjugating enzyme E2 C (UBE2C) also plays a role in regulating the radiosensitivity of breast cancer cells, though the exact mechanism requires further exploration [113].…”
Section: Breast Cancermentioning
confidence: 99%